Dry mass partitioning and nitrogen uptake by Eucalyptus grandis plants in response to localized or mixed application of phosphorus - Graciano, Corina (2009)
Plants respond to nutrient rich patches by changing root morphology and physiology. The aim of this paper was to analyze shoot and root growth of Eucalyptus grandis plants fertilized with the same amount of phosphorus applied in two different ways: thoroughly mixed in the soil or localized in a single hole near the plant. Localized fertilization increased root mass in the zone where fertilizer was applied, but total root mass was not altered by the type of fertilization application. With mixed fertilization plant growth was less than with localized fertilization, and plants showed nitrogen deficiency. Nitrogen uptake was measured in a split-root hydroponics system where phosphate was applied to the whole root system or in part of it. Growth of plants receiving phosphorus in the whole root system was limited by nitrogen uptake, as was revealed by low leaf N and low nitrate uptake. In conclusion, the positive effect of localized application of phosphorus must be ascribed not only to higher phosphorus but also to sustained nitrogen assimilation.